2006
DOI: 10.1111/j.1365-2044.2006.04650.x
|View full text |Cite
|
Sign up to set email alerts
|

Major colorectal surgery in a patient with cold agglutinin disease

Abstract: Summary We present the case of a 62‐year‐old man with severe cold agglutinin disease who underwent major colorectal surgery. Cold agglutinin disease is a condition in which auto‐antibodies, usually immunoglobulin M, cause red blood cell agglutination at decreased body temperature. Haemolysis may result. Agglutination results in impaired perfusion, resulting in symptomatic Raynaud's phenomenon and acrocyanosis. Haemolysis can result in anaemia and thrombotic events caused by microvascular occlusion, in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…32,153 Multiple reports describe an association between acrocyanosis and cold agglutinins, cryoglubulins, or cryofibrinogen. 28,33,154–156 Almost a third of all patients with positive antiphospholipid antibodies have acrocyanosis. 30,40,157,158 Anti-cardiolipin antibodies have been reported in patients with acrocyanosis.…”
Section: Secondary Acrocyanosismentioning
confidence: 99%
“…32,153 Multiple reports describe an association between acrocyanosis and cold agglutinins, cryoglubulins, or cryofibrinogen. 28,33,154–156 Almost a third of all patients with positive antiphospholipid antibodies have acrocyanosis. 30,40,157,158 Anti-cardiolipin antibodies have been reported in patients with acrocyanosis.…”
Section: Secondary Acrocyanosismentioning
confidence: 99%
“…During general anesthesia, heat is lost in a number of ways; predominantly by surface cooling through radiation and convection mechanisms, accounting for up to 40% and 30% of heat loss, respectively. [ 2 ] In light of recognition of these factors, simple measures such as forced-air warming blankets are being increasingly utilised, especially in long duration vascular, plastic, and neurosurgeries to limit the heat loss. However, presence of CAs in surgeries involving deliberate hypothermia, such as cardiac surgery and renal transplantation, pose unique anaesthetic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have previously reported suggestions for the perioperative management during the care of patients with CAD (Table 1) [14][15][16][17][18]. When CAD follows an infectious etiology, elective and non-urgent procedures should be postponed as the antibody titer can be expected to decline over 4 -8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Young et al [14] A 62-year-old male with long-standing, cold agglutinin disease, diabetes mellitus, ischemic heart disease with previous coronary stenting, B-cell in remission, and OSA for an abdomino-peroneal excision of the rectum for a Duke's stage A low rectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%